A cost‐effective video system for a rapid appraisal of deep‐sea benthic habitats: The Azor drift‐cam - Carlos Dominguez‐Carrió; Jorge Fontes; Telmo Morato (Methods in Ecology and Evolution)
Abstract Deep‐sea exploration relies on cutting‐edge technology, which generally requires expensive instruments, highly specialized technicians and ship time. The increasing need to gather large‐scale data on the distribution and conservation status of deep‐sea benthic species and habitats could benefit from the availability of low‐cost imaging tools to facilitate the access to the deep sea world‐wide. Here we describe the Azor drift‐cam, a cost‐effective video platform designed to conduct rapid appraisals of deep‐sea benthic habitats. Built with off‐the‐shelf components, the Azor drift‐cam should be regarded as an effective, affordable, simple‐to‐assemble, easy‐to‐operate, resilient, operational and reliable tool to visually explore the deep sea to 1,000 m depth. Its performance was assessed during the MapGES_2019 cruise, where 135 successful dives between 100 and 800 m depth were carried out in 22 working days, providing over 100 hr of images for almost 80 km of seabed, mostly in areas that had never been explored before. The system does not aim to become a substitute for more sophisticated underwater video and photography platforms, such as ROVs, AUVs or manned submersibles. Rather, it aims to provide the means to perform quick assessments of deep‐sea benthic habitats in a simple and affordable manner. This drift‐cam system has the potential to make deep‐sea exploration more accessible, playing an important role in the Deep‐Ocean Observing Strategy and measuring some of the Essential Ocean Variables for deep‐sea monitoring and conservation strategies.